ANALYSIS OF HUMAN RESOURCE QUALITY DEVELOPMENT IN TERMS OF SELF EFFICACY AND COMPETENCE IN UMKM "AROMANIS COFFEE" TULUNGAGUNG, EAST JAVA - Kuswandi Kuswandi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze the development of the quality of human resources in terms of self-efficacy and competence in the UMKM "Aromanis Coffee" located in Tulungagung Regency, East Java. This research uses descriptive qualitative method. Which interviews with informants are supported by valid data from the Office of Cooperatives and SMEs. The informant in this study was the manager of Aromanis Coffee himself named Mr. Aryo who had been determined by the researchers themselves based on information that could be obtained accurately. Researchers analyzed the quality of human resources in terms of the level of trust and competence of a business group in Indonesia which is considered a strong driver of the country's economy. Judging from the level of human resource education, the condition of MSMEs in the field, the government's efforts to socialize MSMEs, to the limitations they face. The researcher hopes that later with this research, both the government and as economics students can make innovations for common welfare.